DAMPAK SERTIFIKASI TERHADAP PROFESIONALISME GURU (STUDI PEMETAAN (PK) GPAI ON-LINE TINGKAT SMA KOTA PALEMBANG) - Irawadi, Feri; Yustikarini, Listya (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
Certification is one of the breakthroughs to improve teacher professionalism. This means that if the teacher's competence is good, then the performance will be good too. Certification should not be used as an arena for economic improvement, but the event to improve professional competence in teaching. So that certified teachers are professional teachers in educating students. The problem of this study is the impact of PAI SMA teacher certification on professionalism competencies (study of PK Online values). Therefore this study aims to determine the impact of certification on the professionalism of high school teachers in Palembang, which includes Professionalism 1 (material deepening), professionalism (scientific publications), and professionalism 3 (innovative work). This type of research is qualitative descriptive research. The subjects in this study were certified teachers in the city of Palembang and the data used through data documentation. From this study it can be concluded that the implementation of certification followed by certified teachers in the city of Palembang in the Province of South Sumatra under the auspices of the Ministry of Religion. Teachers who have been certified both civil servants and non-civil servants who have received the Ministry of Religion and Ministry of Education in Palembang are 624 people through the PLPG pathway. Teacher's performance before certification cannot be measured. After the PAI teacher competency mapping activities, the competency of PAI and Budi Pekerti teachers was seen in Palembang City. The indicators of teacher professionalism now and in the future are able to make innovations that are realized in the form of scientific publications, material deepening, and innovative work. Existing policies and regulations have set these standards and require every teacher at any level / level to implement them.